Ask the Experts: Dissecting gene–environment contributions to Type 2 diabetes. (September 2012) - Mitchell, Braxton D; Hanson, Robert L
Braxton Mitchell is professor of medicine and of epidemiology & public health at the University of Maryland School of Medicine in Baltimore, MD, USA. He obtained his PhD degree at the University of Michigan, MI, USA. He is a genetic epidemiologist whose research program focuses on assessing the genetic contributions to common age-related diseases, gene mapping and evaluating the impact of discovered variants at the population level. In addition to diabetes, his current research focuses mainly in the areas of cardiovascular disease, stroke, osteoporosis and osteoarthritis. Robert Hanson is staff clinician at the Phoenix Epidemiology and Clinical Research Branch of the National Institute of Diabetes and Digestive and Kidney Diseases in Phoenix, AZ, USA. He obtained his MD degree at the University of Kansas (KS, USA) and his MPH degree at Columbia University (NY, USA). He is an internist and epidemiologist and his research program focuses on the genetic epidemiology of Type 2 diabetes, obesity and complications of diabetes.